ANALISIS PENGARUH KOMUNIKASI, PENGALAMAN KERJA DAN KEMAMPUAN KERJA TERHADAP PROFESIONALISME KARYAWAN PADA BANK SARANA PRIMA MANDIRI PAMEKASAN - Akhmad Supriyadi; Nugroho Mardi Wibowo; Subijanto3, Subijanto (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2021)
The objectives of this research are: 1) To know and describe about communication, work experience, and work ability towards the professionalism of employees at Bank Sarana Prima Mandiri Pamekasan; 2) To find out and test whether communication, work experience and work ability partially have a significant influence on Employee Professionalism at Bank Sarana Prima Mandiri Pamekasan; 3) To determine and test whether communication, work experience and work ability simultaneously have a significant influence on Employee Professionalism at Bank Sarana Prima Mandiri Pamekasan. Data analysis using SPSS. This type of research is explanatory research using a quantitative research approach. The results showed that: 1) Partially, communication, work experience and work ability have a significant influence on Employee Professionalism at Bank Sarana Prima Mandiri Pamekasan. So that in this case the hypothesis is accepted and its validity is proven. This is evidenced by the t value of each independent communication variable (X1) of 1.694 with a significance level of 0.04, work experience (X2) of 1.894 with a significance level of 0.03 and work ability (X3) of 1.418 significance of 0.01. All variables have a significant level less than 0.05 2). Simultaneously, communication, work experience and work ability have a significant influence on Employee Professionalism at Bank Sarana Prima Mandiri Pamekasan. So in this case the hypothesis is accepted and proven to be true, proven by the calculated F value of 4.294 with a significance value of 0.00 which means less than 0.05. In this research, it can be concluded that the dominant result of each independent variable is the communication variable (X1) of 3.152. Thus, the variable that has a dominant effect on the dependent variable is communication.